2010
DOI: 10.1111/ijpp.18.05.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing and sale of ophthalmic chloramphenicol following reclassification to over-the-counter availability

Abstract: Following the reclassification of chloramphenicol there have been significant increases in the supply of the ophthalmic antibacterials in both England and Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…An important difference between the pharmacy sales data utilised in the present study is that whereas data from Company A represented transactions between pharmacy and customers, IMS Health data reported supplies from wholesalers to pharmacies. As with previous studies that have employed IMS Health sales data, the latter was identified to be a good proxy for pharmacy‐to‐customer sales. This relationship is likely to hold for chloramphenicol eye drops as they need to be stored in a fridge, where space is usually at a premium, and bulk advance purchases are unlikely.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…An important difference between the pharmacy sales data utilised in the present study is that whereas data from Company A represented transactions between pharmacy and customers, IMS Health data reported supplies from wholesalers to pharmacies. As with previous studies that have employed IMS Health sales data, the latter was identified to be a good proxy for pharmacy‐to‐customer sales. This relationship is likely to hold for chloramphenicol eye drops as they need to be stored in a fridge, where space is usually at a premium, and bulk advance purchases are unlikely.…”
Section: Discussionmentioning
confidence: 60%
“…The pharmacy sales data presented in this study are the first and the most comprehensive dataset studied to date and include data from all NHS‐contracted community pharmacies in Wales. The results demonstrate that the availability of ophthalmic chloramphenicol OTC has contributed to a greater increase in the supply of chloramphenicol than previously identified . Supplies of OTC chloramphenicol eye drops increased from 2005 to 2007 but have subsequently remained stable.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although patients could obtain the same treatment from a pharmacist as that medically prescribed, the results have shown that a majority of respondents reported no change in the number of prescriptions received for ophthalmic chloramphenicol. In contrast, researchers in the UK found that since the downscheduling in the UK, the number of GP prescriptions for chloramphenicol fell from 2.3 million in 2004 to 1.94 million in 2007, while OTC provision by pharmacists increased [20,21]. This led to an overall increase of 47.8% in total ophthalmic chloramphenicol use at the same time as a decreased GP workload [20,21]…”
Section: Discussionmentioning
confidence: 98%
“…To give some sense of the scale of the potential attendees that could migrate towards emergency secondary care; ->430 million Pharmacists attendances in England annually for health related reasons 4 ->1 million bottles of over-the-counter chloramphenicol are dispensed annually. 5 -16 million optician sight tests / eye examinations performed annually in the UK 6 -340 million GP consultations of which 1.5 -2% are eye related 4 -24 million calls made to NHS urgent telephone services 4 If even small percentages divert to Hospital Eye Service (HES), continuation of the growth experienced in the past decade is possible.…”
Section: Where Is the Increased Demand Coming From?mentioning
confidence: 99%